NK cell-associated long non-coding RNAs reveal heterogeneity of colorectal cancer immune microenvironment - Li, Yuxuan; Xia, Chuqi; Li, Jinze; Qin, Jichao; Shi, Fan; Zhang, Wenkai; Liang, Daoming; Shu, Yixiong; Lu, Qiyu (Frontiers in Immunology, 2025)
IntroductionIndividuals diagnosed with colorectal cancer (CRC) frequently confront a grave prognosis and exhibit poor responses to conventional treatment regimens. Immunotherapy, notably modalities centered on natural killer (NK) cells, represents a burgeoning frontier in the management of CRC. This study developed a validated prognostic model using NK-associated long non-coding RNAs (lncRNAs) to predict CRC outcomes.MethodsIntegrating single-cell RNA-seq (GSE146771_Smartseq2) and TCGA-COAD/READ bulk transcriptomic data, we identified NK-specific genes and correlated lncRNAs. A multi-step analytical approach—including univariate Cox regression for preliminary screening, LASSO regression to minimize overfitting, and multivariate Cox regression for final model optimization—yielded a robust 16-lncRNA prognostic signature with high predictive accuracy. ResultsThis model demonstrated robust predictive performance across the training set, validation set, and 76 independent clinical samples. Mechanistic investigations revealed that AC010319.3 is highly expressed in NK cells, where it attenuates NK cell cytotoxicity by suppressing the expression of IFN-γ and granzyme B, thereby promoting the proliferation and invasion of CRC cells.DiscussionThis study systematically delineates the regulatory role of NK-associated lncRNAs within the CRC immune microenvironment, offering novel molecular targets and stratification strategies for CRC immunotherapy.